2021
DOI: 10.15587/1729-4061.2021.237369
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimal process parameters for sprouting buckwheat as a base for a food seasoning of improved quality

Abstract: In order to determine the influence of temperature and time of germination of the Bogatyr variety buckwheat on a change in the content of vitamins E, C, and B group, the germination parameters were optimized when developing a new type of seasoning. To optimize the germination parameters, the response surface methodology was used. The maximum total content of B, E, and C group vitamins in the sprouted buckwheat (4.591 mg/100 g) was observed at a temperature of 21.5 °C and the duration of germination of 3 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Using the system of mass production of sprouted buckwheat, it is possible to provide the food industry with raw materials rich in linoleic acid, unsaturated fatty acids, free amino acids, rutin, quericitrin, chlorogenic acid, as well as vitamins B 1 , B 6 , C, E [26,27]. Sprouted buckwheat grains are gaining popularity as functional food ingredients [28,29].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Using the system of mass production of sprouted buckwheat, it is possible to provide the food industry with raw materials rich in linoleic acid, unsaturated fatty acids, free amino acids, rutin, quericitrin, chlorogenic acid, as well as vitamins B 1 , B 6 , C, E [26,27]. Sprouted buckwheat grains are gaining popularity as functional food ingredients [28,29].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Interesting work [6] was carried out on the effect of temperature and time of germination of buckwheat variety Bogatyr on changes in the content of vitamins E, C and group B. The results showed that the maximum total content of vitamins B, E and C in germinated buckwheat (4.591 mg/100 g) was observed at a temperature of 21.5 °C and a germination duration of 3 days.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%